Pengaruh Hubungan Orangtua-Anak terhadap Kepercayaan antar Pribadi yang di moderasi oleh Kedekatan dengan Teman Sebaya pada siswa SMA - Haryanti Tri Darmi Titisari (PSIKODIMENSIA, 2017)
Abstract High school students in the adolescence development are influenced by several factors including the environment in physical and psychological development. Attachment to family and friends has an important role in the establishment of trust, including the Interpersonal Trust. Based on that, this study aims to determine the influence of parent and child attachment to interpersonal trust that is moderated by individual attachment to peers. The subjects in this study were high school students on grade 12th as many as 99 students. The study utilized the scale of Parent-Child Relationship, Interpersonal Trust and IPPA, and applied statistics with multiple linear regression techniques. This study shows that Parent and Child Relationship was negatively correlated with Interpersonal Trust, with correlation coefficient of -0.111 and significance value of 0.275 (p> 0,05), indicating that the greater the parent relationship with the child, the less Interpersonal Trust, and vice versa. Nevertheless, the analysis results show that the Moderation Variable (Peer Attachment) was influential, and able to strengthen the relationship between parent and child to Interpersonal Trust.